2005
DOI: 10.4049/jimmunol.174.12.8017
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Genetic Background Is a Major Determinant of Isotype-Related Differences for Antibody-Mediated Protective Efficacy againstCryptococcus neoformans

Abstract: The protective efficacy of mAbs to Cryptococcus neoformans glucuronoxylomannan depends on Ab isotype. Previous studies in A/JCr and C57BL/6J mice showed relative protective efficacy of IgG1, IgG2a ≫ IgG3. However, we now report that in C57BL/6J × 129/Sv mice, IgG3 is protective while IgG1 is not protective, with neither isotype being protective in 129/Sv mice. IgG1, IgG2a, and IgG3 had different effects on IFN-γ expression in infected C57BL/6J × 129/Sv mice. IgG1-treated C57BL/6J × 129/Sv mice had significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
32
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 66 publications
4
32
0
Order By: Relevance
“…Eosinophils have been mentioned before in murine models of cryptococcosis, 10,23,[41][42][43] observed in human cryptococcosis, 44 -46 and described with an emphasis on tissue damage. 41 Although in vitro eosinophils have phagocytosed C. neoformans 23 and presented cryptococcal antigens, 47 in vivo, no evidence for uptake of C. neoformans by eosinophils has been found by others 4 and in this study (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Eosinophils have been mentioned before in murine models of cryptococcosis, 10,23,[41][42][43] observed in human cryptococcosis, 44 -46 and described with an emphasis on tissue damage. 41 Although in vitro eosinophils have phagocytosed C. neoformans 23 and presented cryptococcal antigens, 47 in vivo, no evidence for uptake of C. neoformans by eosinophils has been found by others 4 and in this study (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…C. neoformans infection is associated with increased IgE levels (3,59,60). Given that IgE levels reflect the balance between Th1 and Th2 responses, we measured serum IgE before and after infection in both mouse strains.…”
Section: Vol 75 2007 Mouse Strain Susceptibility To Cryptococcus Nementioning
confidence: 99%
“…Despite considerable evidence that Th2-polarized responses are less protective than Th1-polarized responses, there is conclusive evidence from multiple laboratories that certain antibodies (Abs) affect the course of disease during C. neoformans infection (19,39,49,51,62). The Ab response includes both protective and nonprotective Abs, with the functional quality depending on specificity and isotype as well as on the mouse strain (59,74,75). Further complicating the assessment of humoral immunity are large dose-dependent effects such as the prozone-like effects that can occur in passive Ab experiments, whereby the protective efficacy of the Ab is abrogated in conditions where large doses are administered (67,68).…”
mentioning
confidence: 99%
“…Macrophages and pulmonary dendritic cells rapidly internalize C. neoformans organisms in murine models of pneumonia (17,67); however, in vivo depletion of neutrophils unexpectedly enhanced the host defense (45). B-cell-mediated humoral immunity participates in host resistance against cryptococcal infection (2,57,65), although its protective efficacy depends on the genetic background of the host (56,69,70). A clear role for cytokines such as tumor necrosis factor alpha (TNF-␣), gamma interferon (IFN-␥), interleukin 12 (IL-12), and IL-18, as well as chemokines such as monocyte chemoattractant protein-1 (MCP-1/C-C motif ligand 2 [CCL2]) and macrophage inflammatory protein-1-alpha (MIP-1␣/CCL3) in leukocyte recruitment and effective host defense (33) has been demonstrated.…”
mentioning
confidence: 99%